The use of the cryoprotectant sodium tripolyphosphate as a possible method to minimize weight loss in frozen prawns - Fernando, P.J.M.T.S. (My University, 1988)
A 5% wI I solution of foad grade Sodium Trj~olyph~sphate, N~P:sO.1QJ. 6HzO was used as a dip solution to tre~t partially processed prawns prio~ to freezing. The f t'ozen rrp~n~ ~~re then examined to determine whether dip treatment significantly ~ffe~ted the w~i3ht loss (dr~p lass) in the frozen pr""""",s, rne.!aslJ ""erl I as raw and cooKed )ield. The influence of dip +~~~+~~~t ~~ th~ ~~3a~aleptic and mic,'"ob...c...cgiLal qualities of r~~w~~ w~.e also studied. T~e results indicated that dIp t~~~+-e~t with S~~ium Tripwl,p~osphate signlficantl) reduced the 1-"" igh+ 1£"'<;5 'oJ1'0 i c", is t"'lought to be due to the improvement in \-"..+"'.~ ...~t":!"ltior . T!.e. or3anole~tic and microbiological rk"':>~+~risti~s Oc the dip treated prawns were found to De better tho. +~~ control ~amples.